Employing fuzzy Delphi techniques to validate the components and contents of e-learning antecedents and usage behavior towards e-learning performance - Jabar, Juhaini; Hasim, Mohamad Aidil; Sufian, Atirah; Ibrahim, Nor Fauziana; Abdul Khalid, Fararisha (Eurasian Society of Educational Research, 2023)
The primary objective of this study is to require the experts’ unanimous agreement on the e-learning antecedents and usage behavior towards e-learning performance. This study used the Fuzzy Delphi Method (FDM) to gather answers and feedback using a 7-point Likert scale. The survey (items) was reviewed and approved by eight panel members or experts. It was analyzed using Fuzzy Delphi Logic (FUDELO 1.0) software. The data were evaluated using triangular fuzzy numbering and the position (ranking) of each variable was established through defuzzification. The findings revealed that all of the items received high levels of expert agreement, significantly greater α-cut defuzzification values >.5, the overall value of the threshold (d) is less than .2 and had to comply with the overall percentage of percent consensus, which must be greater than 75%. All 45 recommended items were retained adequately and acceptable for a large-scale survey in this study. Finally, each item was prioritized (ranked) based on the defuzzification value, and then some additional items were added, as recommended by experts.